A supplement to the checklist of the New World chafers (Coleoptera: Scarabaeidae: Melolonthinae) with notes on their tribal classification - Smith, Andrew B.t.; Evans, Arthur V. (Zootaxa, 2005)
The checklist of the New World Melolonthinae published in 2003 by Evans is updated to 30 June 2005. Corrections and omissions to the previous checklist are also noted and necessary taxonomic changes are made. Melolontha elongata Fabricius, 1792 is designated as the type species of Philochloenia Dejean, 1833, syn. nov. thereby placing this genus as a junior synonym of Dichelonyx Harris, 1827. Phyllophaga guatemalica (Moser, 1918), syn. nov. and Phyllophaga longiclava (Moser, 1918), syn. nov. are placed in synonymy with Phyllophaga ravida (Blanchard, 1851). The Australian genus Deuterocaulobius Dalla Torre, 1912, stat. nov. is brought out of synonymy and considered the valid name for “Phyllochlaenia Blanchard, 1846.” Warwickia, nom. nov. is proposed as a replacement name for the junior homonym Benedictia Sanderson, 1939 (non Dybowski, 1875) and consequently, Warwickia pilosa (Sanderson, 1939), comb. nov. is a new combination for the single species in this genus. A brief overview of the tribal classification of Melolonthinae is presented.